2019
DOI: 10.1186/s11671-019-3065-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluid Media on Material Removal and Subsurface Defects Evolution of Monocrystal Copper in Nano-Cutting Process

Abstract: The effect of fluid media on material removal and subsurface defects evolution in nano-cutting process of single-crystal copper is investigated by means of molecular dynamics simulation. In this paper, the removal mechanism of the chip and formation mechanism of machined surface are investigated by analyzing the atomic migration and dislocation evolution of workpiece during nano-cutting process with the use of aqueous media. The distribution of temperature and subsurface defect crystal structural transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Whether the water was applied on the second half of the surface or the full surface, a consistent 26% reduction in cutting force and 23% reduction in thrust forces can be observed. The reduction in cutting forces with applied water is consistent with the conclusions reached through MD simulations . Additional benefits of water application can be seen through improvements in machined surface quality where a lower roughness of 0.876 μm R a can be obtained with applied water as compared to normal cutting that produces a roughness of 1.328 μm R a (Figure b).…”
Section: Physicochemical Surface Implications On Microlevel Deformationsupporting
confidence: 82%
See 2 more Smart Citations
“…Whether the water was applied on the second half of the surface or the full surface, a consistent 26% reduction in cutting force and 23% reduction in thrust forces can be observed. The reduction in cutting forces with applied water is consistent with the conclusions reached through MD simulations . Additional benefits of water application can be seen through improvements in machined surface quality where a lower roughness of 0.876 μm R a can be obtained with applied water as compared to normal cutting that produces a roughness of 1.328 μm R a (Figure b).…”
Section: Physicochemical Surface Implications On Microlevel Deformationsupporting
confidence: 82%
“…Researchers are, therefore, heavily reliant on theoretical calculations and simulations to identify the root causes for the experimental findings. In the context of water on copper, previous reports have largely focused on lubrication, cooling, , and microcorrosion effects, as detailed in Table .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dislocation distribution in chip was perpendicular to the cutting direction when the cutting direction is ( 1 1 0) [1 1 0]. Wang et al [20] studied the influence of fluid media on chip formation process of single crystal copper. It is found that the presence of water causes the hot zone in the chip to move from the tool-chip contact zone to the top of the chip.…”
Section: Introductionmentioning
confidence: 99%
“…The subsurface defects not only solely affect the processing accuracy and surface quality, but also critically affect the mechanical properties and service life of nano-components. Many studies about subsurface defects have been carried out by molecular dynamics (MD) method, mainly focusing on the formation and evolution of subsurface defect s[6, 7], the thickness of subsurface defects (SSD) layer [8, 9], and the influence subsurface defects on surface integrity [10, 11]. However, the effect of subsurface defects on mechanical properties of workpiece materials is less studied.…”
Section: Introductionmentioning
confidence: 99%